Multi-wavelength laser generation based on nonlinear effects in PCF and Bi-EDF / Roghaieh Parvizi - Parvizi, Roghaieh (2012)
This thesis describes multi-wavelength laser generation process based on stimulated Brillouin scattering (SBS) and four-wave mixing (FWM) nonlinear effects utilizing photonic crystal fibre (PCF) or/and Bismuth based Erbium doped fibre (Bi-EDF) as the gain medium. Firstly, the threshold power condition of SBS for a piece of100 m long PCF has been theoretically studied in terms of fibre parameters and input pump power. The threshold exponential gain, Gth, can be anticipated by this simulation which strongly depends on the fibre length Brillouin gain content and effective area. This value varies from 14 to 18 depending on the fibre length according to the Smith’s definition. The frequency shift of Brillouin Stokes in the PCF is measured nearly 9.75 GHz via heterodyne measurement method. In order to reduce the nonlinear fibre length, 49 cm long Bi-EDF is used, which successfully demonstrates a single wavelength Brillouin Erbium fibre laser (BEFL) with a peak power of approximately -4 dBm and a side mode suppression ratio (SMSR) of 14 dB in a ring cavity at fixed Brillouin pump (BP) power of 6 dBm and 1480 nm pump power of 144 mW. A simple multi-wavelength Brillouin fibre laser (BFL) is also demonstrated using the PCF in conjunction with a fibre Bragg grating (FBG) to produce at least 7 Stokes and 4 anti-Stokes lines with a line spacing of 0.08 nm. To produce doublespacing Brillouin lines, a compact multi-wavelength Brillouin fibre laser in conjunction with a figure-of-eight configuration is proposed. At a BP power of 15.3 dBm, at least 4 simultaneous lines with 20 GHz or 0.16 nm line spacing is achieved by removing the oddorder Stokes lines. The anti-Stokes lines are also generated via FWM process in the laser cavity. The output spectrum of the proposed BFL can be tuned by 80 nm, dependent on the availability of an appropriate BP source. To increase the number of lines and channel spacing, a multi-wavelength Erbium doped fibre laser (MWEDFL) is demonstrated with incorporating a piece of 215 cm long Bi-EDF through FWM process in a ring configuration. The proposed laser is able to generate up to 17 lines with a constant channel spacing of 0.41 nm at L-band region using 147 mW of 1480 nm pump power. The other stable MWEDFL based on FWM using a hybrid gain media of 100 m long PCF and 49 cm long Bi-EDF fibre is demonstrated. At a maximum pump power of 1480 nm, 5 lines are observed with nearly 2.15 nm spacing between the lines, and with a signal to noise ratio of more than 20 dB. These results show that the use of a highly nonlinear PCF and Bi-EDF is capable to produce a compact and efficient multi-wavelength laser for many applications such as wavelength division multiplexing system (WDM) optical communication network system and sensors.